PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA: (Studi Kasus Pada Perusahaan Manufaktur Sektor Industri Dasar Tahun 2016 - 2020) - ANDRIA REFERLI,; IRVAN ZAINUDIN,; YUNITA NIQRISAH DWI P , (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2022)
The purpose of this study is about the effect of Good Corporate Governance on earnings management (a case study on a manufacturing company in the basic industrial sector for the period 2016-2020). Calculated with discretionary accruals. The population is manufacturing companies that have been listed on the Indonesia Stock Exchange (IDX). The method of analysis in the form of multiple regression. Using data from manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020 as many as 24 sample companies. The results of this study are the independent committee variable partially positive, significant effect on earnings management. In some cases, the audit committee has a positive and insignificant effect on earnings management and managerial ownership partially has a negative and insignificant effect on earnings management. Fcount 4,969 > Ftable 2.68 with an alpha level of 5% then Ho is rejected and Ha is accepted because the value of sig 0.003 is smaller than alpha 0.05, so it is concluded that all variables simultaneously affect the dependent variable. The R2 test has an influence between all independent variables on the dependent variable, namely 11%.